The Tasks Ahead. (IMF Working Papers; Working Paper, 2008)
This note, prepared ahead of the G20 Summit (November 15), builds upon the points laid out in the Managing Director's letter to the Heads of State and Government (November 9). It lays out two tasks ahead for policy makers. Policies for now should cover:(i)implementing and coordinating policies to sustain demand; (ii) providing liquidity support to emerging economies; and (iii) protecting low-income countries. Longer term reforms of the financial architecture should touch upon:(i) the design of financial regulation; (ii) a better way of assessing systemic risk; and (iii) mechanisms for more effective actions for crisis prevention and resolution.